Religious Moderation in Minority Muslim Community Interactions: A Talcott Parsons Structural Functionalist Approach - Toton Fanshurna; Isnadi Isnadi (Eduvest - Journal of Universal Studies, 2025)
This study explores the practice of religious moderation within the framework of interreligious social interaction in Rejoagung Village, Jember, East Java, a community distinguished by its unique demographic composition of a Christian majority and a Muslim minority. Employing a qualitative approach with an intrinsic case study design, the research identifies forms of social engagement that embody the principles of religious moderation. Data were gathered through in-depth interviews, field observations, and participatory documentation, and analyzed using Talcott Parsons’ structural functionalism framework with a particular emphasis on the AGIL scheme (Adaptation, Goal Attainment, Integration, and Latency). The findings reveal that religious moderation in Rejoagung is rooted not merely in formal tolerance but in deeply internalized shared values embedded within the village’s social fabric. This harmony is maintained through cross-group adaptation, sustained collaborative activities, and the leadership of influential local figures who reinforce social cohesion. The study offers a context-specific contribution to the discourse on religious moderation by illustrating how the synergy between cultural norms, religious ethics, and local institutional practices can serve as a sustainable foundation for peaceful coexistence in a diverse society.